Influence of Tax Socialization, Services, and Trust on Compliance via Tax Knowledge - Nuryadi, Nuryadi; Cahyono, Dwi; Sanosra, Abadi (SENTRALISASI, 2024)
Taxpayer compliance is crucial for effective tax administration and national development. This study aims to evaluate the direct and indirect effects of tax socialization, tax services, and trust in government on taxpayer compliance, with tax knowledge serving as a mediating variable, in Jombang Subdistrict, Jember Regency. Utilizing a quantitative research approach, data were collected from a sample of 376 respondents out of a total of 6,302 taxpayers, determined using the Slovin formula with a 5% margin of error. Structural equation modeling was employed to analyze the relationships among the variables. The results indicate that tax socialization, tax services, and trust in government significantly and positively impact both tax knowledge and taxpayer compliance. Tax knowledge was found to mediate these relationships, enhancing taxpayer compliance. These findings highlight the need for effective tax education programs, high-quality tax services, and efforts to build trust in government to improve taxpayer compliance. Future research should explore the applicability of these findings in other regional contexts and investigate additional mediating factors. Implementing tailored tax education initiatives and improved service delivery models could significantly enhance compliance rates and support broader economic and social goals.